Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Minat Belajar Siswa Tunanetra Sekolah Menengah Pertama Luar Biasa - Ida Aulia Mawaddah; Muhammad Parhun; Abdul Haris (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study discusses the strategies of Islamic Religious Education teachers to increase the learning interest of blind students in class VIII of SMP SLBN 1 Sumbawa. This study was motivated by the low interest in learning of students who are limited in the use of methods, media and learning strategies that are not yet adaptive. The research method used is descriptive qualitative, with data acquisition using observation, interview and documentation techniques, while the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study show that the strategies implemented by Islamic Religious Education teachers include the use of systematic verbal explanations, the use of audio media, the use of braille, and creating an inclusive learning environment. These strategies have been proven to be able to increase the involvement of blind students in Islamic Religious Education learning.